The Influence of Knowledge Management and Organizational Culture through Employee Engagement as a Mediation Variable on Millennial Employee Performance at the Center for Education and Training Center for Statistics Indonesia - Angeline Junita Monica; Renny Husniati; Yudi Nur Supriadi (Garuda Prestasi Nusantara Consulting, 2023)
Abstract The most important resource of an organization is human resources, so employees are the key to determining the success of the organization. Performance is the result of work achieved by an employee in carrying out tasks according to responsibility. The performance of employees at the Center for Education and Training of the Central Statistics Agency is considered to be still not optimal, as can be seen from the quality of work that has not met the expectations of the leadership. The purpose of this study is to prove that there is an influence between Knowledge Management and Organizational Culture Through Employee Engagement as a Mediation Variable on Millennial Employee Performance. The research method is a survey method to 31 employees, by distributing questionnaires which are answered with statements of the Likekert scale model. The analysis technique is path analysis and hypothesis testing with the help of Smart PLS software.that knowledge management, organizational culture, has a significant effect on employee performanceAndemployee engagementcommitment has a positive and significant effect on organizational culture and also on employee performance. Suggestions aremust pay attention again to how to apply knowledge management so that all employees, especially millennial employees, can have high performance and competitiveness in the midst of industry 4.0 and can further improve organizational culture, especially from aggressive factors through spaces to give opinionsand brilliant ideas for the organization, can also increase employee engagement withespecially the dedication in doing the job. For example, by providing a variety of jobs that are challenging but also inspiring so that millennial employees feel proud to do them. Keywords: Knowledge Management, Organizational Culture,employee engagement,employee performance